Understanding B2B Consumer Satisfaction Through Perceptual and Cognitive Lenses: A Case Study of Geotronix Indonesia - Adi, Fajar Setio; Lestari, Esti (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: The B2B survey technology industry struggles to merge behavioral analytics with technical performance. Limited empirical use of consumer behavior theories exists in industrial procurement, especially in Southeast Asia. Purpose: This study examines behavioral factors influencing customer satisfaction at Geotronix Pratama Indonesia. It integrates Solomon’s Consumer Perception Model and Peter & Olson’s Cognitive Processing Model to build behaviorally driven customer profiles. Methodology: A convergent mixed-methods approach was employed. Data were collected from 50 client surveys and eight stakeholder interviews. Pearson correlation tested relationships, while NVivo-based thematic analysis provided qualitative insights. Findings: Equipment quality strongly correlates with satisfaction (r = 0.67, p < 0.01). Technical support shows moderate correlation (r = 0.34, p < 0.05). Reliability shapes initial perceptions, while support fosters long-term trust. Satisfaction drivers shift from product performance to partnership value as relationships mature. Conclusion: Satisfaction in B2B procurement is driven by both tangible perceptions and cognitive service evaluations. Firms should balance product quality and proactive support within behavior-based CRM strategies that adapt to client relationship stages. Originality/value: This study pioneers the dual application of Solomon’s and Peter & Olson’s models in Southeast Asian B2B contexts. It offers a validated framework linking perception, cognition, and industrial customer satisfaction. Keywords: customer satisfaction, consumer behavior, b2b marketing, survey technology, mixed-methods research